Methodological essence of the innovative project - Mekhovych, K. S.; Mekhovych, E. S.; Pererva, P. G. (ТОВ "Юридична компанія "Юрсервіс", 2023)
Projects are mainly used in the implementation of investments, but this approach is widespread in the implementation of organizational and technological innovations. Knowledge and skills related to projects and their proper management are necessary in any modern managed organization. In addition, the importance of this issue has increased with the attempt to join the European Union Ukraine.
Keywords: innovative activity; project management; economy; efficiency; enterprises